2002
DOI: 10.1159/000048306
|View full text |Cite
|
Sign up to set email alerts
|

Age-Corrected Normal Values for Perimetry

Abstract: Purpose: Age-corrected values are indispensable in assessing discrete changes in light difference sensitivity (LDS) when evaluating perimetric results. In order to detect incipient visual field defects, the present study aimed particularly to determine function of normal values depending on age and eccentricity. Methods: A test group (n = 83) of ophthalmologically and clinically unremarkable subjects 18–74 years of age was examined with the ‘Centerfield’ perimeter. A brief introductory program was first used t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 9 publications
1
4
0
1
Order By: Relevance
“…Age also affected perimetric luminance thresholds, as was expected on the basis of previous normative data (Becker, Vonthein, Volpe, & Schiefer, 2005; Wohlrab, Erb, & Rohrbach, 2002). Mean luminance thresholds increased with age [ANOVA: F(7, 86) = 12.46, p < .001, η 2 = .50], with participants in their 60s, 70s, and 80s, in particular, having significantly higher average perimetric thresholds than the remainder of the sample.…”
Section: Resultssupporting
confidence: 80%
“…Age also affected perimetric luminance thresholds, as was expected on the basis of previous normative data (Becker, Vonthein, Volpe, & Schiefer, 2005; Wohlrab, Erb, & Rohrbach, 2002). Mean luminance thresholds increased with age [ANOVA: F(7, 86) = 12.46, p < .001, η 2 = .50], with participants in their 60s, 70s, and 80s, in particular, having significantly higher average perimetric thresholds than the remainder of the sample.…”
Section: Resultssupporting
confidence: 80%
“…For Compass, the mean decrease was -0.048 dB / year for the foveal and perifoveal areas, and -0.045 dB / year for the central 10°. For HFA, other published sources report a mean decrease of-0.047 dB / year for the foveal area [ 15 ] and of-0.041 dB / year for the central 10° [ 14 ].…”
Section: Resultsmentioning
confidence: 99%
“…A study by Leeprechanon et al [22] showed an AROC of second-generation FDT and SWAP in the detection of PPG (0.74 for MD of SWAP and 0.67 for PSD of FDT). Brusini et al [12] reported that optimal specificity was found in detecting early glaucomatous visual field defects when at least one area with a non-hit rate of [70 % was used as a cutoff criterion An age-related decline in sensitivity was reported [12,[14][15][16][17][18], and the decline with aging was even more pronounced using a smaller target [8]. Salvetat et al [24] reported a normative range for rarebit perimetry and showed a significant inverse linear relationship between the mean hit rate and age.…”
Section: Discussionmentioning
confidence: 99%
“…An age-related decline of sensitivity in the visual field was reported previously [14][15][16][17][18]. From the 60 normal participants, we selected control subjects matched for age (average difference of ±5 years) and sex for comparison with the PPG and POAG groups.…”
Section: Control Subjectsmentioning
confidence: 99%